Determination of the fibrinogenolytic activity of Montivipera raddei (Raddeʼs mountain viper) venom - Atasoy, Fikriye Seda; İğci, Naşit (Archives of Biological Sciences, 2022)
Paper description: Snake venom fibrinogenolytic enzymes have diagnostic and therapeutic value and are important for snakebite pathology. There is no study in the literature investigating the fibrinogenolytic activity of Montivipera raddei venom. SDS-PAGE and zymography were used to assess fibrinogen degradation. HPLC was used to obtain supportive data. The presence of fibrinogenolytic serine and metalloproteinases in M. raddei venom is reported in in vitro experiments. The presented findings will guide future studies aiming to identify new fibrinogenolytic enzymes and evaluate their biotechnological potential. The results will be useful for the assessment of snakebite pathology. Abstract: Snake venom fibrinogenolytic enzymes have diagnostic and therapeutic value and are important for snakebite pathology. In the present study, the fibrinogenolytic activity of Montivipera raddei venom was investigated. Crude venom was incubated with human fibrinogen for different times at 37°C. An inhibition study was carried out using different protease inhibitors. The fibrinogenolytic activity was assessed by SDS-PAGE and fibrinogen zymography. An HPLC-based method was used to obtain confirmatory data. Montivipera raddei venom predominantly cleaved the Aα chain of fibrinogen in a time-dependent manner. A very slight decrease in band intensity of the Bβ chain was observable after a longer incubation time. Cleavage of fibrinogen was confirmed by HPLC. Zymography revealed that the venom contained 50 and 75 kDa fibrinogenolytic enzymes. Ethylenediaminetetraacetic acid (EDTA) and 1,10-phenanthroline inhibited the overall fibrinogenolytic activity, while phenylmethylsulfonyl fluoride (PMSF) and aprotinin only inhibited the degradation of the Bβ chain. These results indicated that metalloproteinases were major fibrinogenolytic enzymes in the venom. An inhibitor study suggested the presence of serine proteinases that broke down the Bβ chain. With this study, the fibrinogenolytic activity of M. raddei venom was shown for the first time. The results will be useful for further isolation and characterization studies.